Organizational Culture And Performance: Testing A Moderated Mediation Model Of Commitment And Job Satisfaction - Maulana Akbar (PT PUSTAKA CENDEKIA GROUP, 2025)
This study examines organizational cultural relationships, organizational commitment, job satisfaction, and performance in personnel of the Directorate of Special Criminal Investigation of the South Sulawesi Police. The researcher used a quantitative approach with a survey method and collected data from one hundred respondents who met the research criteria. The researcher used a closed-ended questionnaire based on a five-point Likert scale to capture respondents' perceptions of each variable in a measurable manner. The researcher compiles an instrument from the relevant indicators, then conducts validity and reliability testing before the main analysis. The researcher analyzed data using SEM PLS with SmartPLS through the evaluation of measurement models and structural models, including testing the role of organizational commitment as a mediator and job satisfaction as a moderator on organizational cultural relations and performance. The results of the study showed that job satisfaction did not have a significant direct effect on performance. Organizational culture has a positive and significant influence on performance, and is the main determinant that drives organizational commitment. Organizational commitment also has a positive and significant influence on performance, so commitment plays an important role as an important path that channels the influence of organizational culture towards performance. Moderation testing shows that job satisfaction strengthens the formation of organizational commitments, so that strengthening organizational culture results in a stronger commitment when the level of job satisfaction is higher. These findings emphasize that the focus of improvement needs to be directed at the consistency of work culture and strengthening commitment, as well as improving aspects of job satisfaction that support the attachment of personnel to the organization.